Effects of halogenated hydrocarbons on the respiration of beef heart mitochondria and submitochondrial particles - Kewley, Carolyn Florence (Division of Chemical Pathology, 2020)
The investigations to be presented in this thesis arose from studies on the respiration of mitochondria isolated from pig skeletal muscle. These animals developed the syndrome of Malignant Hypermedia after exposure to halothane - a halogenated hydrocarbon used as an inhalation anesthetic agent.